2022
DOI: 10.21037/atm-22-1028
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressants or corticosteroids compared with supportive therapy: a systematic review and meta-analysis on the efficacy and safety for IgA nephropathy treatment

Abstract: Background: Corticosteroids or immunosuppressants and supportive treatment in reducing the risk of proteinuria and end-stage kidney disease (ESKD) in immunoglobulin A (IgA) nephropathy (IgAN) patients were still controversial. The purpose of this meta-analysis was to evaluate the efficacy and safety of immunosuppressants or corticosteroids compared with supportive therapy for treatment of IgAN in order to provide guidance for clinical practice. Methods:We conducted an online search in PubMed, Embase, Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…The role of corticosteroid intervention for IgAN remains debated [21][22][23]. In the STOP-IgAN trial, immunosuppressive therapy for high-risk IgAN patients did not signi cantly improve the outcome, and more adverse effects were observed [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The role of corticosteroid intervention for IgAN remains debated [21][22][23]. In the STOP-IgAN trial, immunosuppressive therapy for high-risk IgAN patients did not signi cantly improve the outcome, and more adverse effects were observed [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis ( 48 ) included 58 relevant studies revealed that corticosteroid treatment probably improved clinical outcomes in adults and children with IgA nephropathy and proteinuria. A lately published meta-analysis ( 49 ) reported that corticosteroids combined with immunosuppressants might significantly reduce the risk of proteinuria and end-stage kidney disease in IgAN patients. However, adverse events under oral steroids treatment should be acknowledged, especially in those with high-dose therapy.…”
Section: Discussionmentioning
confidence: 99%
“…La GEFS es el patrón de lesión glomerular más frecuente encontrado en biopsias renales en los Estados Unidos y América Latina 6 , siendo la principal causa de síndrome nefrótico y de enfermedad renal crónica (ERC) en estadio terminal secundaria a glomerulopatía primaria en población blanca, afroamericana y latina 3,7 . Además, es considerada como una de las glomerulopatías con mayor incidencia en el mundo (unos 0.8-1.4 casos por cada 100,000 hab/año) [4][5][6] , solo por debajo de la nefropatía por inmunoglobulina A (unos 2.5 casos por cada 100,000 hab/año) 8 . Se distinguen tres formas clásicas: -La GEFS primaria o idiopática, que responde a la lesión podocitaria causada por un factor circulante «permeabilizador», probablemente asociado a una respuesta autoinmunitaria mediada por linfocitos T y B. Esta postura es fuertemente respaldada por estudios recientes que evidencian el papel de la respuesta humoral, específicamente la producción de autoanticuerpos contra la podocina, en el desarrollo de síndrome nefrótico en pacientes con podocitopatías como la enfermedad de cambios mínimos 9,10 .…”
Section: Introductionunclassified